EVALUASI EFEKTIFITAS CLOSED CIRCUIT TELEVISION DALAM FUNGSI PENINGKATAN PENGAWASAN TERMINAL KARGO DI BANDAR UDARA BATAM - Betanio Ferry Bintang Utama; Abdul Mu'ti Sazali; Dewi Ratnasari (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Hang Nadim International Airport Batam is one of the airports in Indonesia that serves both domestic and international routes. As an airport that serves international flights, the rapid development of cargo has resulted in an increasingly crowded and congested cargo delivery rate. The writer found problems that related to the lack and effectiveness of Closed Circuit Television (CCTV) facilities in the supervision carried out by the Inspector Terminal unit. The Cargo Terminal has a huge area that engerders supervision in the cargo terminal area is carried out by the Airport Inspector Terminal unit which is not only responsible for the terminal area. The purpose of this study is to evaluate the effectiveness of CCTV facilities in the supervision carried out by the Inspector Terminal. there is still a lack of CCTV facilities in the cargo area so that there is a buildup of goods and reduces the monitoring performance of the Terminal Inspector unit. The existence of CCTV facilities in the cargo area and adding CCTV in areas that haven’t been covered can increase the supervision carried out by the Inspector Terminal.